2022
DOI: 10.3892/ijmm.2022.5197
|View full text |Cite
|
Sign up to set email alerts
|

HIF‑1α: Its notable role in the maintenance of oxygen, bone and iron homeostasis (Review)

Abstract: Hypoxia is a characteristic feature of numerous diseases, including metabolic bone disease, solid tumors, cardiovascular diseases, neurodegeneration and inflammation. It is also a risk factor for a poor prognosis in various diseases. Hypoxia-inducible factor-1α (HIF-1α) is activated by hypoxia to regulate a series of pathophysiological pathways, which is of utmost significance for maintaining body homeostasis. The present review highlights the role of the HIF-1α in oxygen, bone and iron homeostasis, and allude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…In the cell, this is achieved in two different directions: HIF1α increases the expression of glucose transporters, while the energy sensor AMPK increases glucose import via the Akt2/Glut4 pathway. Both proteins are activated by iron depletion [ 116 , 167 ], thereby causing iron deficiency and, further on, anemia. Supporting these physiological approaches to activate HIF1α by HIF-prolyl hydroxylase inhibitors or AMPK by metformin [ 164 ] might prevent anemia [ 169 ] and protect from mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cell, this is achieved in two different directions: HIF1α increases the expression of glucose transporters, while the energy sensor AMPK increases glucose import via the Akt2/Glut4 pathway. Both proteins are activated by iron depletion [ 116 , 167 ], thereby causing iron deficiency and, further on, anemia. Supporting these physiological approaches to activate HIF1α by HIF-prolyl hydroxylase inhibitors or AMPK by metformin [ 164 ] might prevent anemia [ 169 ] and protect from mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxia, the hydroxylation of the alpha subunits is inhibited, thus stabilizing the HIF1α subunits [ 115 ]. HIF1α, together with HIF1ß, constitutes a transcription factor for several thousand genes and shifts cell metabolism towards oxygen-independent glycolysis [ 116 ]. Two of its target genes code for Glut1 and Glut3.…”
Section: Cellular Mechanisms To Cope With the Energy Crisismentioning
confidence: 99%
“…HIF-1 is a crucial regulatory protein that controls oxygen homeostasis and plays a primary role in managing the balance between oxygen supply and demand [24]. Under lowoxygen conditions, the hypoxic environment triggers the synthesis of HIF-1, which then regulates angiogenesis, erythropoiesis, and glycolysis to restore oxygen equilibrium [25]. To comprehend the oxygen requirements necessary to govern the physical environment of a particular tissue, it is imperative to understand oxygen tension in the tendon [26,27].…”
Section: Role Of Hif-1 In Tendonsmentioning
confidence: 99%
“…In this study, HIF1A was identified as a key upstream regulator of parathyroid volume and function. HIF, a group of transcription factors, plays a role in the body's response to hypoxia by activating genes that encourage blood vessel growth and anaerobic glycolysis [52]. However, it has been shown that HIF1A expression and the expression of HIF1A-driven genes can be controlled in various ways that do not depend on oxygen [53].…”
Section: Ipa Canonical Pathwaymentioning
confidence: 99%